The Influence Of Leadership Agility, Motivation, And Organizational Culture On Job Satisfaction And The State Civil Apparatus (SCA) Performance At The Office Of The Ministry Of Religion In West Papua Province - Bambang Sunatar (Journal Research of Social Science, Economics, and Management, 2023)
Agility leadership is expected to improve the performance and satisfaction of The State Civil Apparatus (SCA) employees and can play a positive role in motivating employees and building a positive organizational culture. Agility leadership is the ability to identify, find and engage stakeholders. Motivation encourages an understanding of The State Civil Apparatus (SCA) goals that employees want to achieve. Organizational culture also has a positive and significant effect on Agility Leadership. This quantitative research uses a SEM-PLS approach. Quantitative research is the search for explanations and universal laws that are formulated in a quantitative approach that is more directed at things that are general in nature. Based on the results of the study, the researchers concluded that Agility leadership had a major effect on The State Civil Apparatus (SCA) satisfaction and performance at work.